Detection of rotavirus by counterimmunoelectrophoresis in cases of infantile diarrhea - Candeias, J. A. N.; Rosenburg, Cornélio P.; Rácz, M. L. (Revista de Saúde Pública, 1978)
The faecal samples of 162 children with acute diarrhea were tested by counterimmunoelectrophoresis in order to detect rotaviruses. In 72.7%, 77.7% and 66.6% of samples from children of different age groups, varying from 6 to 8 months to 1 year or older, a positive result was found.